Cortisol inhibits CSF2 and CSF3 via DNA methylation and inhibits invasion in first‐trimester trophoblast cells. (28th August 2017) - Smith, Arianna; Witte, Elizabeth; McGee, Devin; Knott, Jason; Narang, Kavita; Racicot, Karen
Abstract : Problem: Heightened maternal stress affects trophoblast function and increases risk for adverse pregnancy outcomes. Methods of Study: Studies were performed using the first‐trimester trophoblast cell line, Sw.71. Cytokines were quantified using qPCR and ELISA. Epigenetic regulation of cytokines was characterized by inhibiting histone deacetylation (1 μmol/L suberoylanilide hydroxamic acid [SAHA]) or methylation (5 μmol/L 5‐azacytidine), or with chromatin immunoprecipitation (ChIP) with a pan‐acetyl histone‐3 antibody. Invasion assays used Matrigel chambers. Results: Cortisol inhibited expression of CSF2 (GM‐CSF) and CSF3 (G‐CSF) in trophoblast cells. Cortisol‐associated inhibition was dependent on DNA methylation and was not affected by acetylation. There was also a modest decrease in trophoblast invasion, not dependent on loss of CSFs. Conclusion: In first‐trimester trophoblast cells, the physiological glucocorticoid, cortisol, inhibited two cytokines with roles in placental development and decreased trophoblast invasion. Cortisol‐associated changes in trophoblast function could increase the risk for immune‐mediated abortion or other adverse pregnancy outcomes.